Corporate governance and firm performance: do shariah-compliant companies on bursa Malaysia exhibit good corporate governance? - Foo, Pek Juan (2022)
The purpose of this study is to explore whether there is any significant relationship between corporate governance and financial performance of Shariah-compliant companies in Consumer Products and Services sector listed on Bursa Malaysia and whether they exhibit good governance. By examining the board’s characteristic of 100 Shariah-compliant companies in Consumer Products and Services sector of Bursa Malaysia’s Main Market against firm performance using annual data from 2011 to 2020. The analysis clearly showed that companies that applied MCCG practices in their operations improved their performance overall. The presence of BSIZE, BIND, BMEET, WDIR and MDIR have positive impact on the financial performance. On the other hands, presence of CEO Duality has significant negative impact on the firms’ financial performance. These could believe that Shariah-compliant companies in Consumer Products and Services sector listed on Bursa Malaysia has exhibit good governance. On the other hands, this study provides theoretical contributions to demonstrate the nature of corporate governance theories and the Shariah-compliance in Malaysia. Therefore, it has filled the gaps in literature sources studying the association between corporate governance and company’s performance from the perspective of Shariahcompliant companies in Consumer Products and Services sector.